Dongeng “Dunia Mangrove” Berbasis Augmented Reality untuk Melestarikan Objek Wisata Pesisir bagi Anak Usia Dini - Eriqa Pratiwi; Tarich Yuandana; Nosia Khosiyana (Universitas Trunojoyo Madura, 2023)
The development of the world of early childhood education is currently increasing rapidly marked by the use of learning media that prioritizes technology such as fairy tales based on augmented reality. However, the use of technology-based learning media such as fairy tales based on augmented reality is still limited. This is based on the results of observations at the age of 4-6 years who live around the Labuhan mangrove education park. The fairy tale